The effect of encounter in the experimental novel : (A stylistic study in Jamal Al- Ghitani’s Tajalliyat novel) - Al- Shawi, Bassam Khaled; Hayek, Zainab Walid (Arab Journal for Sciences and Research Publishing, 2021)
The point of the analysis that the researcher intends to study the effect of convergence in the novel (Al- Tajjayat) as an experimental novel that relied on the amazing Sufi experience is to reveal the style of Jamal Al- Ghitani from the face that distinguishes him from others. Correspondence, during the analysis of samples of the texts of the novel, and after the research examined the contrast in the main elements of the novel (the narrator’s discourse, characters, and time It was found that correspondence in (Al- Tajjayat) is one of the components of style in building the miraculous world in this novel, and its effectiveness in producing meaning, and highlighting the mystical experience, so that this stylistic component contributes to the transition from the eloquence of the sentence to the eloquence of the text. At the end of the research, the researcher recommended studying other exquisite components in the novel (Al- Tajjayat) to reveal the role of exquisite composition in the construction of the method in this novel.